KESESUAIAN EKOWISATA MANGROVE DITINJAU DARI ASPEK BIOGEOFISIK KAWASAN PANTAI GONDA DI DESA LALIKO KECAMATAN CAMPALAGIAN KABUPATEN POLEWALI MANDAR - Sadik, Muhammad; Muhiddin, Amir Hamzah; Ukkas, Marzuki (Jurnal Ilmu Kelautan SPERMONDE, 2017)
Ecotourism is a nature-based tourism activity that includes aspects of education and interpretation of the natural environment and community culture with ecological sustainability management. This study aims to determine the bioecological aspects of mangrove ecosystem as an object of ecotourism and to know the geophysical aspects of Gonda Beach as a supporter of mangrove ecotourism suitability on Gonda Beach. This research was conducted in November 2016 in Laliko Village, Campalagian Sub-district, Polewali Mandar Regency, including mangrove bioecological data collection including thickness, density, species and biota associated with mangrove and coastal geophysical data collection covering wide coastal measurement, coastal slope, depth, tidal, current, wave and substrate of waters. Result of research show potential of mangrove ecosystem to become ecotourism area with good condition of mangrove vegetation. The mangrove species in the ecosystem of the gonda mangroves are Bruguiera gymnorrhiza, Rhizophora stylosa, Rhizophora apiculata, Ceriops tagal, Sonneratia alba, Avicennia alba, Avicennia marina, Xylocarpus granatum and Xylocarpus moluccensis, and diverse biota such as fish, reptiles, birds and crabs as a tourist attraction . Gonda mangrove ecosystem area is a very suitable area to become a mangrove ecotourism area.Keywords: ecotourism, mangrove, conformity analysis, tourism object